ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT SURABAYA TERHADAP PENGGUNAAN DOMPET DIGITAL GOPAY - Febrina Rahardi; Novi Marlena (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to determine, explain, and analyze whether cultural, social, personal, psychological, price, place, promotion, and product factors affect the interest of the people of Surabaya city and also want to know whether the dominant factor influences the interest of Surabaya people in using the Gopay digital wallet. In this study, the population used was all Gopay digital wallet users in the city of Surabaya using the "purposive sampling" sampling technique method using the Lemeshow formula for determining the sample in this study obtained 103 respondents. The analysis used, factor analysis. Multiple linear regression calculations in this study used the SPSS 29.0 for windows program. The results showed that there were 4 factors formed, namely place, product, social, and personal. The place factor is the dominant factor based on the eigenvalue of 13.353 with a cumulative value of 51.358%. Keywords: Gopay; Fintech; Culture; Social; Individu; Price; Place; Promotion; Product